Ehrliche Unehrlichkeit Eine qualitative Untersuchung der Tugend Ehrlichkeit bei Jugendlichen an der Zürcher Volksschule - Chiapparini, Emanuela (Verlag Barbara Budrich, 2012)
Using virtue as an example, the study provides an insight into the normative and subjective orientations of young people in their everyday school context. The concept of virtue in previous educational debates is juxtaposed with a perspective that incorporates the students' point of view: In contrast to the normatively used concept of virtue, the present findings present virtue of honesty as an ambivalent behavior that is situation-, context- and person-dependent. Since ancient Greece, virtues have been a central theme of pedagogy. Educational philosophers have repeatedly developed catalogues of virtues which they assumed could guide practical education. The present work asks how young people adapt to educational demands and undermine them to their own advantage. The question is pursued using the example of school-relevant virtue honesty by interviewing 16 young people in the school context using problem-centred interviews. The results of the study refer to explicit and implicit rules of honesty, which can be divided into conventional and unconventional rules.